Rocks and minerals - Parker, Steve (New York : DK Pub., 1997)
Photographs, illustrations and text teach children about the different types of rocks and minerals and how they are made, with simple experiments to help readers learn more about certain types of rocks and the processes that make them.
Includes index.
5.4.
5.4
3-6
Keywords: Minerals -- Juvenile literature; Rocks -- Juvenile literature; Minerals; Rocks; Minerals; Rocks